A Transitivity Analysis of some Compounds in Computer Networking Jargon (International Journal of Scientific Research and Management (IJSRM), 2022)
There have been numerous attempts by linguists to investigate into the ideational function of language. However, most researches concerning transitivity analysis base themselves only on the clause. Scant attention has been paid to compounds, as linguistic devices that can be used to see how the experience of computer networking is represented. This study uses Hallidayan transitivity to analyze some compounds found in computer networking jargon, as most of the words in it are compound nouns. The study aims to identify how language is manipulated by computer networking persons to construe the experience of computer networking. To conduct this study, a sample of 166 was drawn from the population of 262 compounds that were collected from different books on computer networking. The collected compounds were those expressing technical terms of computer networking. The findings reveal that mental processes are not used to construe the experience of computer networking. By contrast, material processes and relational processes are used to construe the experience of computer networking. These processes are realized in different configurations.